One half mile from heaven - Stanley, Francis Louis (Denver, Colorado World Press Publishing Co., 1949)
This is a rough draft of the book One half mile from heaven or the Cimarron Story compiled by F. Stanley ( Francis Louis Stanley). About the history of how Cimarron came to be.
g
Mater List Item # 85
File location is in the New Mexico File Cabinets
Keywords: Local History; Settlement History; Origin Story; Southwest History; Gunfights; Landgrants; Murders; Cimarron, New Mexico